Pharmacogenomic Response of Inhaled Corticosteroids for the Treatment of Asthma: Considerations for Therapy - Cazzola M; Rogliani P; Calzetta L; Matera MG (Dove Medical Press, 2020)
Mario Cazzola,1 Paola Rogliani,1 Luigino Calzetta,2 Maria Gabriella Matera3 1Unit of Respiratory Medicine, Department of Experimental Medicine, University of Rome “Tor Vergata”, Rome, Italy; 2Unit of Respiratory Disease and Lung Function, Department of Medicine and Surgery, University of Parma, Parma, Italy; 3Unit of Pharmacology, Department of Experimental Medicine, University of Campania “Luigi Vanvitelli”, Naples, ItalyCorrespondence: Mario Cazzola Email mario.cazzola@uniroma2.itAbstract: There is a large interindividual variability in response to ICSs in asthma. About 70% of the variance in ICS response is likely due at least partially to genetically determined characteristics of target genes. In this article, we examine the effects on the ICS response of gene variations in the corticosteroid pathway, and in the pharmacokinetics of corticosteroids, and also those outside the corticosteroid pathway, which have the potential to influence corticosteroid activity. Although the available evidence indicates that responses to ICSs in asthma are influenced by different genetic variants, there are still deep uncertainties as to whether a real association between these genetic variants and corticosteroid response could also possibly exist because there are difficulties in reproducing pharmacogenetic findings. This explains at least partly the insufficient use of pharmacogenomic data when treating asthmatic patients, which creates a real limitation to the proper use of ICSs in an era of precision medicine that links the right patient to the right treatment. Knowing and dealing with the genetic factors that influence the therapeutic ICS response is a fundamental condition for prescribing the right dose of ICS to the right patient at the right time.Keywords: asthma, inhaled corticosteroids, gene polymorphisms, genome-wide association studies, precision medicine